Exploring the Dynamic Interplay between Note-Taking Strategies and Reading Comprehension Performance of Moroccan EFL Students: A Quasi-Experimental Study - Koumachi, Bani (Research in English Language Teaching, 2020)
Recently, at Moroccan tertiary level and in the area of student practices, little attention has been brought particularly to the skill of note-taking and active reading comprehension, and an insightful and in-depth understanding of how students learn from lectures could presumably be valuable in understanding and unraveling the intricacies of possible positive results of their note-taking behavior. The current study focuses mainly on the instruction of students into the systems of note-taking and how that affects their level of reading comprehension. Therefore, the effort reported here attempts to assess the students’ current systems of note taking and how they contribute to reach a full understanding of reading comprehension texts. The participants were 94 Semester-One students at the department of the English Studies at Ibn Tofail University, School of Arts and Humanities in Kénitra, Morocco. The data of the present study were collected by means of a TOEFL iBT Reading Practice comprehension test (i.e., post-test), and strategy training equating note-taking schemas and reading comprehension texts. The findings have showcased there is a significantly positive relationship between note-taking strategies and active reading comprehension. Even though there has been no special given to a specific system of note taking, it has been obvious empirically that the use of certain note-taking system is liable to positively influence the retention of comprehension texts.